In vitro analysis of polypeptide requirements of multicomponent phenol hydroxylase from Pseudomonas sp. strain CF600. - Powlowski, J (1990)
An in vitro study of the multicomponent phenol hydroxylase from Pseudomonas sp. strain CF600 was performed. Phenol-stimulated oxygen uptake from crude extracts was strictly dependent on the addition of NAD(P)H and Fe2+ to assay mixtures. Five of six polypeptides required for growth on phenol were necessary for in vitro activity. One of the polypeptides was purified to homogeneity and found to be a flavin adenine dinucleotide containing iron-sulfur protein with significant sequence homology, at the amino terminus, to plant-type ferredoxins. This component, as in other oxygenase systems, probably functions to transfer electrons from NAD(P)H to the iron-requiring oxygenase component. Phenol hydroxylase from this organism is thus markedly different from bacterial flavoprotein monooxygenases commonly used for hydroxylation of other phenolic compounds, but bears a number of similarities to multicomponent oxygenase systems for unactivated compounds.